Natural variation in WHITE-CORE RATE 1 regulates redox homeostasis in rice endosperm to affect grain quality. Issue 5 (16th February 2022) - Wu, Bian; Yun, Peng; Zhou, Hao; Xia, Duo; Gu, Yuan; Li, Pingbo; Yao, Jialing; Zhou, Zhuqing; Chen, Jianxian; Liu, Rongjia; Cheng, Shiyuan; Zhang, Hao; et al.
Abstract: Grain chalkiness reduces the quality of rice ( Oryza sativa ) and is a highly undesirable trait for breeding and marketing. However, the underlying molecular cause of chalkiness remains largely unknown. Here, we cloned the F-box gene WHITE-CORE RATE 1 ( WCR1 ), which negatively regulates grain chalkiness and improves grain quality in rice. A functional A/G variation in the promoter region of WCR1 generates the alleles WCR1 A and WCR1 G, which originated from tropical japonica and wild rice Oryza ruﬁpogon, respectively. OsDOF17 is a transcriptional activator that binds to the AAAAG cis-element in the WCR1 A promoter. WCR1 positively affects the transcription of the metallothionein gene MT2b and interacts with MT2b to inhibit its 26S proteasome-mediated degradation, leading to decreased reactive oxygen species production and delayed programmed cell death in rice endosperm. This, in turn, leads to reduced chalkiness. Our findings uncover a molecular mechanism underlying rice chalkiness and identify the promising natural variant WCR1 A, with application potential for rice breeding. Abstract : The chalkiness gene WHITE-CORE RATE 1 regulates redox homeostasis in rice endosperm by interacting with the metallothionein MT2b, thereby affecting grain quality.